The Improvement of Students’ Activities and Outcomes on English Language Subject on Writing Descriptive Material Through Discovery Learning Model at The Eleventh Science 3 Grade State Islamic Senior High School 1 Banjarmasin Academic Year 2016/2017 - Mariani, Mariani Mariani (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2018)
This research aims to know the activities and learning outcomes of students on writing descriptive text material through the model Discovery Learning in class XI MIA 3 MAN 1 Banjarmasin Lesson 2016/2017. This research used Action research method. Subjects were 36 students consisting of 21 female students and 15 male students. Discovery Learning has a positive impact in improving students’ learning achievement which is marked by the improvement of students’ learning completeness in every cycle, improving student learning outcomes marked by the improvement of students’ learning mastery in each cycle, that is, there are 14 students (42.4 %) of completed students increased in cycle II to 29 students (87,9%).